2017
DOI: 10.1007/s13197-017-2742-1
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin stability and color change of krill during subcritical water treatment

Abstract: Pacific krill () contains high amounts of astaxanthin, a carotenoid pigment with strong antioxidative activities. In this study, the effects of subcritical water temperatures (100-180 °C) and times (0-10 min) on color changes (*, *, and*) and astaxanthin degradation in Pacific krill were investigated. In addition, an aqueous solution of pure astaxanthin and that of crude astaxanthin from Pacific krill, both at a concentration of 5 mg/L, were subjected to treatment under subcritical water conditions using a flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…A good correlation existed between the AST content and red color of dried shrimps as reported by Niamnuy et al . After the shrimp was heat processed, browning occurred as a result of a higher rate of the Maillard reaction . Kchaou et al .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A good correlation existed between the AST content and red color of dried shrimps as reported by Niamnuy et al . After the shrimp was heat processed, browning occurred as a result of a higher rate of the Maillard reaction . Kchaou et al .…”
Section: Discussionmentioning
confidence: 52%
“…A good correlation existed between the AST content and red color of dried shrimps as reported by Niamnuy et al 13 After the shrimp was heat processed, browning occurred as a result of a higher rate of the Maillard reaction. 37 Kchaou et al 38 also reported the effect of Maillard reaction on browning of fish. Furthermore, Cyprian et al 39 reported a relationship between the depth of sardine yellowness and the accumulation of lipid oxidation products such as hydroperoxides and aldehydes such as malondialdehydes, some of which could react with amines, amino acids and proteins to result in browning in many fatty foods during processing.…”
Section: Discussionmentioning
confidence: 98%
“…In adonirubin and adonixanthin, five and seven Z ‐isomer peaks were observed, respectively, which were identified by absorption maxima, shape of spectrum, and relative intensities of the Z ‐peak to the absorption maximum of the isomer (% D B /D II ) (Table 1 and Figure 2; Figures S2,S4, Supporting Information). [ 32,34,36–44 ]…”
Section: Resultsmentioning
confidence: 99%
“…Adonirubin, astaxanthin, and adonixanthin isomers were analyzed by normal‐phase HPLC with a photodiode array detector (SPD‐M20A; Shimadzu, Kyoto, Japan) according to the previously described method with some modifications. [ 36–39 ] Briefly, the analysis was conducted using two Phenomenex silica gel columns connected in tandem (Luna 5 µm Silica (2), 2 × 150 mm × 4.6 mm, 100 Å) and the mobile phase consisted of hexane/ethyl acetate/acetone (70:20:10, v/v/v). The flow rate and column temperature were set at 1.2 mL min −1 and 40 °C, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation